Kinetics of cross-slope running - Willwacher, S.; Fischer, K. M.; Benker, R.; Dill, S.; Brüggemann, G. P. (Journal of Biomechanics, 2013)
The purpose of the present study was to identify kinetic responses to running on mediolaterally elevated (cross-sloped) running surfaces. Ground reaction forces (GRFs), GRF lever arms and joint moment characteristics of 19 male runners were analyzed when running at 3.5 m/s on a custom-made, tiltable runway. Tilt angles of 3° and 6° for medial and lateral elevation were analyzed using a 10 camera Vicon Nexus system and a force platform. The point of force application of the GRF showed a systematic shift in the order of 1-1.5 cm to either the lateral or medial aspect of the foot for lateral or medial inclinations, respectively. Consequently, the strongest significant effects of tilt orientation and level on joint kinetics and ground reaction force lever arms were identified at the ankle, knee and hip joint in the frontal plane of movement. External eversion moments at the ankle were significantly increased by 35% for 6° of lateral elevation and decreased by 16% for 6° of medial elevation. Altering the cross-slope of the running surface changed the pattern of ankle joint moments in the transversal plane. Effect sizes were on average larger for laterally elevated conditions, indicating a higher sensitivity of kinetic parameters to this kind of surface tilt. These alterations in joint kinetics should be considered in the choice of the running environment, especially for specific risk groups, like runners in rehabilitation processes.